Study on the Dynamic Biological Characteristics of Sca-1+ Hematopoietic Stem and Progenitor Cell Senescence - Shan Geng; Xin-Yi Mu; Xiong-Bin Chen; Ji-Ying Hou; Dao-Yong Jia; Chun-Yan Xu; Ya-Ping Wang (Stem Cells International)
The researches in the dynamic changes of the progress of HSCs aging are very limited and necessary. In this study, male C57BL/6 mice were divided into 5 groups by age. We found that the superoxide damage of HSPCs started to increase from the middle age (6 months old), with notably reduced antioxidation ability. In accordance with that, the senescence of HSPCs also started from the middle age, since the self-renewal and differentiation ability remarkably decreased, and senescence-associated markers SA-β-GAL increased in the 6-month-old and the older groups. Interestingly, the telomere length and telomerase activity increased to a certain degree in the 6-month-old group. It suggested an intrinsic spontaneous ability of HSPCs against aging. It may provide a theoretical and experimental foundation for better understanding the senescence progress of HSPCs. And the dynamic biological characteristics of HSPCs senescence may also contribute to the clinical optimal time for antiaging drug intervention.